SISTEM PENUNJANG KEPUTUSAN PRIORITAS PERBAIKAN JALAN MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS - Ade Mubarok; Astri Rosmiati (Jurnal Informatika, 2016)
Abstract Bina Marga and Irrigation Bandung Department was one of the government agencies in the field of public works, which place the development of infrastructure, including field bina marga and water resources became one of the development priority for managing Bandung. The roadwork was committed because there were road damage. Handling roadwork often had problems and needed handling priority of roadwork. The method used for roadwork priority, namely Analytical Hierarchy Process (AHP) method. By the decision support system to determine the priority of roadwork using AHP could help to assess the priority and make the right decisions with better judgment. Based on the results of this study concluded that the presence of decision support systems in the form of a website, it could be overcome delay in processing, faster and easier in determine priority of roadwork, processing and storage of data were integrated by database. Keywords: Decisions, Road, Priority.